Physical And Chemical Characterization Of Tin In Amang From West Coast Peninsular Malaysia - Zabidi, Muhammad Afiq (Universiti Sains Malaysia, 2018)
The purpose of this research is to characterize and identify the tin from amang from west coast peninsular Malaysia. There are two different places of samples obtained in this research, which from Gunung Paku and Lembah Kinta , Perak. Seven methods of characterization were implemented in this research such as particle size distribution, moisture content, loss on ignition, elemental composition (using XRF), phase identification (using XRD), microscopy study (using scanning electron microscopy, energy dispersive X-ray and ore microscopy) and tin assay. From this research, both of samples shown the existence of cassiterite (SnO2) and other heavy minerals such as ilmenite (FeTiO3), rutile (TiO2), hematite (Fe2O3) and monazite [(Ce, La, Y, Th)PO4]. Besides, sample from Gunung Paku shown high contamination of sulphur and arsenic. Referred to the liberation analysis, for -75µm size fraction, the percentages of liberated particles for the sample from Lembah Kinta was 85.91% while for sample from Gunung Paku was 80.24%. Therefore, the sample from Lembah Kinta was slightly more weathered than sample from Gunung Paku. There were some interlocking mineral with each other especially in coarse size particles. Most of the crystal habits were found for both samples are in irregular shape such as ilmenite and monazite. Based on the tin assay analysis, the percentage of tin content inside the sample from Gunung Paku was 0.44% and not profitable to be recover because less than 0.5% while for sample from Lembah Kinta, the percentage of cassiterite was 0.97% and it was economical to be extract.